The Dynamics of the Knowledge Economy: Innovation, Challenges, And the Future Economy of Time - Patel, Paraskumar (Journal of Educational Research and Policies, 2025)
Peter Drucker's concept of a knowledge - based economy remains relevant as it emphasizes the significance of advanced scientific research in driving innovation and economic growth. This paper explores methods to accelerate innovation and addresses the critical distinction between innovation and knowledge. By examining the roles of various industries and the evolution of economic sectors, the paper highlights the importance of continuous knowledge flow for entrepreneurship and innovation. The discussion extends to the potential of the quinary economy and the future implications of knowledge transfer and weaponization. The paper concludes with strategic recommendations for enhancing knowledge resilience, leveraging knowledge for national and international competitiveness, and preparing for the next stage of economic evolution: the time - based economy.